The Path of the Reformed Church in Elizabeth - NAGY, Péter (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The Hungarian Reformed Church in Elizabeth, New Jersey operated for about sixty years. The congregation was established by Hungarian immigrants to the United States of America in the late 19th and early 20th centuries. On 21 May 1914, the church became member of the Presbyterian Church in the United States of America. The close-knit community had an active religious and social life and became an important meeting place for local Hungarians. The congregation, which had become financially independent, organized a number of charity events to finance their own expenses, missionary goals, and fundraising activities. It was also important for the congregation to cultivate its Hungarian roots. In the 1970s, it had to cease independent operation partly due to the assimilation of the second and third generations and partly because of urban planning due to the change in the social composition of the town. Rev. Bertalan Szathmáry, a pastor who had previously served in the Elizabeth congregation for several years, gathered the leaderless Newark congregants and founded a new congregation in Union.